Come un Ministro per la cultura Giulio Einaudi e le biblioteche nel sistema del libro - Faggiolani, Chiara (Biblioteche & bibliotecari / Libraries & librarians, 2020)
Elegant, lofty, charming, brilliant, bellicose, refined, capricious, superb, temerarious, vain. Giulio Einaudi is an oxymoron. From the extensive literature that has furthered our understanding of his figure, he emerges as the synthesis of divergent behaviours and contrasting inclinations. This oxymoron translates in the features of his publishing house, which integrates diachronicity and current affairs, tradition and newness, scientificity and militancy. The book deepens our knowledge of one of the most neglected aspects of Giulio Einaudi's outstanding service towards Italian culture: namely his promotion of public libraries in the 1960s in Italy. Our starting point is the establishment of Dogliani's civic library, dedicated to his father the President Luigi Einaudi. Setting out from this event - which we have retraced with a particular eye towards oral history - the book proposes to rethink the relationship between Einaudi's view on library project and his cultural programme, which he expressed in the same years through an intense political campaign for the promotion of public access to reading.